(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Origins of Human Nature - Foundation for Human Rights. The article addresses the issue of human rights as a natural and natural expression of human dignity, willed by the Creator and as a special position of man in divine creation. Therefore, he presented arguments, logical, historical and theological regarding the necessity, viability and greatness of human rights as deriving from the will of God and being the expression of His glory.